The effect of sonication on the photoluminescence property of carbon quantum dots synthesized by hydrothermal route - Ochoa, D.; Guzmán Torres, J.; Cervantes, E. M.; Cavazos, J. L.; Gómez, I. (2024)
Due to their chemical and physical properties, this study focuses on the effect of sonication over carbon quantum dots synthesized by means of hydrothermal route, having as precursor the sour lemon juice from Michoacán, Mexico. The exfoliation was carried out with a sonotrode in times of 1, 2 and 3 hours to provide an explanation over the effect of it on the photoluminescence, where it was found that with times of 1 hour, the PL emission is improved resulting from 261 a.u. to 448 a.u. Other characterizations were carried out to confirm the results obtained in PL, where the average particle size was analyzed by SEM, particle sizes ranging from 5 to 11 nm were observed, with an average size of 7.5 nm and to confirm the carbonaceous material, UV-Vis was performed showing a resolved UV absorption band around 340 nm.